FISH BONE PERFORATION OF SMALL BOWEL MIMICKING ACUTE APPENDICITIS - Islam, Shariful; Maughn, Anthony; Harnarayn, Patrick; Naraynsingh, Vijay (International Journal of Research -GRANTHAALAYAH, 2016)
Accidental ingestion of foreign bodies is a commonly encountered event in clinical practice. However, small bowel perforation due to a fish bone is a rare phenomenon. Often, the exact diagnosis is missed preoperatively and is revealed only at laparotomy. Delay in diagnosis and treatment can be associated with significant morbidity and mortality. We report a case of 54- year male who presented with right lower quadrant pain with nausea and vomiting. Clinically, Acute appendicitis was diagnosed. Computerized tomography (CT) of the abdomen confirmed pockets of free air in the right lower quadrant with fat streaking suggestive of perforated ileum. On exploratory laparotomy, the ileal perforation was confirmed secondary to a fish bone. Although rare, foreign body perforation of the small bowel should be entertained in the differential diagnosis in certain groups of patients presenting with acute abdomen.